Analisis System Application Product (SAP) di PTPN III Kebun Dusun Hulu - Senly Ardalena Damanik; Nurlaila Nurlaila (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research uses a qualitative research method with a case study approach. In this research, researchers found that the technical system used for SAP at PTPN III Kebun Dusun Hulu has sufficient capacity and can work properly. However, some technical problems such as network errors, damage to hardware, or software that is not working properly can hinder the data input process. Based on the research results, researchers found that PTPN III Kebun Dusun Hulu had implemented several efforts and solutions to overcome obstacles to the System Application and Product (SAP). One of them is ensuring accurate and transparent recording and reporting of human resources, thereby helping plantations manage and utilize human resources effectively and efficiently. Apart from that, refreshment activities were also carried out for employees to understand the importance of business process standardization in SAP and how to apply it consistently. There are also routine supervision and monitoring activities to ensure correct understanding and implementation of business processes by all employees.